Pengaruh Derajat Sosoh dan Pengemas terhadap Mutu Beras Aromatik selama Penyimpanan - Tarigan, Elsera Br; Kusbiantoro, Bram (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Aromatic rice is popular for its aroma, taste, and texture. The chemical compound of 2-Acetyl-1-pyrrolina (2AP) contributes to the pandan leaf-like aroma, while the hexanal compound is used as an indicator of rancidity in rice. Grains of three aromatic rice varieties, namely Mentik Wangi, Pandan Wangi, and Sintanur were milled in three degree of milling, i.e., 100, 90, and 0% (brown rice). The milled rice and the brown rice were then stored in hermetic bags and plastic bags for 4 months at room temperature. Chemical composition of the packed and stored rice grains were determined by the proximate analysis, including moisture content, ash content, fat content, protein content, and amylose content. The analysis was conducted at the beginning and the end of month of storage. Consumer preference test of the packed rice was done by the hedonic test. Moisture, ash, protein and fat contents during storage were still in the standards range. Compared to the amylose content prior to storage, the textures of the cooked rice after four months of storage remained fluffier or became less fluffy. The aroma, tenderness, texture, flavor, and overall attributes, judged by the panelists, Mentik Wangi was the most favored, followed by Sintanur and Pandan Wangi. Both hermetic bag and plastic bag gave no different effects on the stored rice quality and on the consumer preferences.